Long‐term safety and effectiveness of berotralstat for hereditary angioedema: The open‐label APeX‐S study. Issue 4 (18th June 2021) - Farkas, Henriette; Stobiecki, Marcin; Peter, Jonny; Kinaciyan, Tamar; Maurer, Marcus; Aygören‐Pürsün, Emel; Kiani‐Alikhan, Sorena; Wu, Adrian; Reshef, Avner; Bygum, Anette; Fain, Olivier; Hagin, David; et al.
Abstract: Background: Berotralstat (BCX7353) is an oral, once‐daily inhibitor of plasma kallikrein recently approved for prevention of angioedema attacks in adults and adolescents with hereditary angioedema (HAE). The objective of this report is to summarize results from an interim analysis of an ongoing long‐term safety study of berotralstat in patients with HAE. Methods: APeX‐S is an ongoing, phase 2, open‐label study conducted in 22 countries (ClinicalTrials.gov, NCT03472040). Eligible patients with a clinical diagnosis of HAE due to C1 inhibitor deficiency (HAE‐C1‐INH) were centrally allocated to receive berotralstat 150 or 110 mg once daily. The primary objective was to determine long‐term safety and the secondary objective was to evaluate effectiveness. Results: Enrolled patients ( N  = 227) received berotralstat 150 mg ( n  = 127) or 110 mg ( n  = 100) once daily. The median (range) duration of exposure was 342 (11–540) and 307 (14–429) days for the 150‐mg and 110‐mg groups, respectively. Treatment‐emergent adverse events (TEAEs) occurred in 91% ( n  = 206) of patients. The most common TEAEs across treatment groups were upper respiratory tract infection ( n  = 91, 40%), abdominal pain ( n  = 57, 25%), headache ( n  = 40, 18%), and diarrhea ( n  = 31, 14%) and were mostly mild to moderate. Fifty percent ( n  = 113) of patients had at least one drug‐related adverse event (AE; 150 mg, n  = 57 [45%]; 110 mg, n  = 56 [56%]), and discontinuations due to AEs occurred in 19 (8%) patients (150 mg, n  = 13 [10%]; 110 mg, n  = 6 [6%]). Three (1.3%) patients experienced a drug‐related serious TEAE. Among patients who received berotralstat through 48 weeks (150 mg, n  = 73; 110 mg, n  = 30), median HAE attack rates were low in month 1 (150 mg, 1.0 attacks/month; 110 mg, 0.5 attacks/month) and remained low through 12 months (0 attacks/month in both dose groups). Mean HAE attack rates followed a similar trend, and no evidence for patient tolerance to berotralstat emerged. In both dose groups, angioedema quality of life scores showed clinically meaningful changes from baseline. Conclusions: In this analysis, both berotralstat doses, 150  and 110 mg once daily, were generally well tolerated. Effectiveness results support the durability and robustness of berotralstat as prophylactic therapy in patients with HAE. Trial registration: The study is registered with ClinicalTrials.gov (NCT03472040).